Vitamin D Level and Vitamin D Receptor Genetic Variation Were Involved in the Risk of Non-Alcoholic Fatty Liver Disease: A Case-Control Study - Zhang, Ru; Wang, Minxian; Wang, Min; Zhang, Liuxin; Ding, Yajie; Tang, Zongzhe; Fu, Zuqiang; Fan, Haozhi; Zhang, Wei; Wang, Jie (Frontiers in Endocrinology, 2021)
Background: It has been demonstrated that vitamin D receptor (VDR), a key gene in the metabolism of vitamin D (VD), may affect the development of Non-alcoholic fatty liver disease (NAFLD) by regulating VD level and its biological effects. Objectives: To investigate the effects of serum VD level, VDR variation, and a combination of VDR SNP and environmental behavior factor on the risk of NAFLD. Methods: A total of 3023 subjects from a community in Nanjing were enrolled, including 1120 NAFLD cases and 1903 controls. Serum 25(OH)D3 levels were measured and eight single nucleotide polymorphisms (SNPs) in VDR gene were genotyped. Results: Logistic regression analyses indicated that VD sufficiency and VD insufficiency were significantly associated with a low risk of NAFLD (all P<0.05; all Ptrend <0.05, in a locus-dosage manner). After adjusting for gender and age, VDR rs2228570-A and rs11168287-A alleles were all reduced the risk of NAFLD (all PFDR=0.136, in dominant model; Ptrend =0.039, combined effects in a locus-dosage manner). The protective effects of two favorable alleles were more evident among subjects ≤40 years, non-hypertension, non-hyperglycemia and non-low high density lipoprotein-cholesterol (all P<0.05). The area under the receiver operating curve (AUROC) of the combination of VDR SNP and exercise time for assessing NAFLD risk was slightly higher than that of only including exercise time or neither (all P<0.05). Conclusion: High serum VD levels and VDR variants (rs2228570-A and rs11168287-A) might contribute to a low risk of NAFLD in Chinese Han population. The inclusion of VDR SNP and exercise time could improve the efficiency in assessment of NAFLD risk, which might provide a novel perspective for early screening and preventing NAFLD.